Gene expression analysis during the conversion from a viable but nonculturable to culturable state in Vibrio cholerae - Ayibieke, Alafate; Nishiyama, Ayae; Senoh, Mitsutoshi; Hamabata, Takashi (Gene, 2023)
[Display omitted] •Transcriptomic changes of V. cholerae VBNC during resuscitation are described.•Resuscitation of VBNC cells begins 2 h after catalase treatment.•Resuscitated cells start to proliferate 6 h after catalase treatment.•Stress response related genes are upregulated in the early resuscitation process. We previously reported that Vibrio cholerae in a viable but non-culturable (VBNC) state can be converted to a culturable state by treatment with catalase. This finding enabled us to develop an assay system to observe the time course of the conversion from VBNC to culturable in V. cholerae. VBNC cells began to convert to culturable cells as early as 2 h after catalase supplementation. Gene expression in VBNC cells during catalase treatment was analyzed using RNA microarray. Many ribosomal DNA genes were stimulated 6 h post catalase exposure, suggesting that the conversion-driving signal started prior to 6 h. Focusing on the period prior to cell proliferation, we found that 16 genes might be involved in the conversion mechanism in V. cholerae, and they showed enhanced expression at 2 h and 4 h after catalase addition. These upregulated genes included phage shock proteins (pspA, B, and C), alternative sigma factor (rpoE) and its negative regulator (rseA), cobW C terminal domain-containing protein, damage-inducible helicase (dinG), cholerae toxin secretion protein epsM, HTH-type transcription regulator (iscR), mechanosensitive ion channel family protein, anthranilate synthase component I, fructose-specific IIBC component, molybdenum import ATP-binding protein (modC), LysE family translocator, putative organic hydroperoxide resistance protein, and a hypothetical protein. This study identified genes involved in the catalase-induced conversion of V. cholerae VBNC cells to a culturable state and provided valuable insights into the mechanisms involved in the conversion process.